Decision of Professional Musical Methods in the Oral Tradition - Isaqova Zulfizar Sharabitdinovna (International Journal on Orange Technologies, 2021)
in this article, information about the spiritual heritage left by our ancestors, “teacher-shogird tradition”, the performing teacher-shogird tradition, the art of singing, the Uzbek national musical heritage is highlighted. The legacy of great scientists is based on the decision-making of professional music styles in oral tradition.